Dissipative, Entropy-Production Systems across Condensed Matter and Interdisciplinary Classical VS. Quantum Physics - Gadomski, Adam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The thematic range of this book is wide and can loosely be described as polydispersive. Figuratively, it resembles a polynuclear path of yielding (poly)crystals. Such path can be taken when looking at it from the first side. However, a closer inspection of the book's contents gives rise to a much more monodispersive/single-crystal and compacted (than crudely expected) picture of the book's contents presented to a potential reader. Namely, all contributions collected can be united under the common denominator of maximum-entropy and entropy production principles experienced by both classical and quantum systems in (non)equilibrium conditions. The proposed order of presenting the material commences with properly subordinated classical systems (seven contributions) and ends up with three remaining quantum systems, presented by the chapters' authors. The overarching editorial makes the presentation of the wide-range material self-contained and compact, irrespective of whether comprehending it from classical or quantum physical viewpoints.